A study on glycogen content of endometrial glands in infertile women (Journal of Pathology of Nepal, 2021)
Background: Infertility is a public health problem worldwide. One of the important factors involved in infertility is the poor quality of endometrium which leads to death of the ovum before and after implantation. Glycogen is known to be a direct source of nutrients for the early conceptus and its depletion may result in inadequate preparation of endometrium around the time of implantation and leading to infertility. Materials and methods: This is a prospective study conducted at a tertiary care hospital for 2 years. The study included 75 cases of infertility (primary and secondary). Relevant data were collected from all the 75 biopsied infertile cases during the study period. Periodic acid Schiff stain was performed on all cases to detect the amount of glycogen in the endometrium. The findings were compiled, analyzed, and compared with other studies.Results: Primary infertility accounted for 77.3%and Secondary infertility 22.7% of the 75 cases. On histology, anovulatory cycles accounted for 52% of cases. In the remaining cases, 38.7% showed secretory phase, 4%cases each showed luteal phase defect and hyperplasia, and 1.3% tubercular endometritis. Glycogen content of the endometrium was (1+) in 54.6%, (2+) in 9.3%, (3+) in 9.3% and (4+) in 26.8% in the infertility patients.Glycopenia was seen in 12% of the 75 cases studied.Conclusions: Endometrial factors are important causes of infertility and depletion of glycogen, that can be corrected by hormonal therapy to improve the fertility potential needs to be evaluated in all cases of infertility.